Fighting Wars, Killing People: New Media And Awareness Of Gaza-Israeli 2023 War - Ifeanyi Martins NWOKEOCHA, PhD (Citakonsultindo, 2024)
The recurring Israeli-Palestinian war has entered a new phase of narrative shaping with the advent of new media. This work provides an examination of new media awareness on the conflict, offering insights into its dual capacity as a tool for both unity and division. Social media platforms like TikTok, Instagram, Twitter, YouTube, Facebook were used by the warring factions in disseminating information about the war. These platforms empowered activists and citizens to broadcast their experiences and mobilize support, yet they equally facilitate the spread of disinformation and incitement. The paper is based on qualitative research method, where books, journals and other printed materials were reviewed. The paper argues for the mindful and strategic use of social media, urging a balance between harnessing its power for constructive dialogue and curbing the risks of exacerbating tensions. The agenda setting theory was used for the work. It was recommended that media houses should not wait for conflicts to escalate before creating awareness or reporting about them.